Testicular cancer and HPV semen infection - Garolla, Andrea; Pizzol, Damiano; Bertoldo, Alessandro; Ghezzi, Marco; Carraro, Umberto; Ferlin, Alberto; Foresta, Carlo (Frontiers in Endocrinology, 2012)
Testicular cancer represents the more frequent solid tumour affecting males aged 15-35 years. In the last decades, its incidence showed a progressive increased probably due to genetic and environmental factors. Despite exposure to some viruses such as HIV, HCV, EBV and HPV is frequently related to cancer development, there are no studies aimed to evaluate the possible implication of viral infections in the pathogenesis of testicular cancer. In this study we analyzed sperm parameters and prevalence of HPV on sperm in 155 testicular cancer patients at diagnosis (T-1), after orchiectomy (T0) and after 12 months from surgery or from the end of adjuvant treatments (T12). All patients showed a significantly higher prevalence of semen infection than controls (9.5% and 2.4% respectively) and altered sperm parameters both at T-1 and T0. Considering sperm parameters, at T-1 we observed a reduction of progressive motility, and after orchiectomy patients showed a reduction of sperm concentration and count and a further worsening of motility. Thereafter, patients were assigned to three groups on the basis of medical option after surgery: S = surveillance, R = radiotherapy and C = chemotherapy +/- radiotherapy. At T12, untreated patients had an improvement of sperm parameters while R group and even more C group had a strong decrease of sperm number (p<0.01 both vs T0 and S group). Moreover, patients who received radio and/or chemotherapy had a very high prevalence of HPV semen infection (S: 7.7%, R: 30.8% and C: 61.5%). In conclusion, patients with testicular cancer had frequently altered sperm parameters and higher prevalence of HPV semen infection that were worsened after radio and chemotherapy. Because HPV infection is a risk factor for cancer development and it may further reduce fertility, we suggest screening for HPV in testicular cancer patients at diagnosis and particularly after adjuvant treatments.